The Representation of Femininity in Womens’ Beauty Advertising - Nupus, Hayati (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This article explores the depiction or reflection of women through various signs that contain meaning, namely language and visual communication aimed at the general public (consumers in an advertisement). This study aims to discuss the visual and linguistic elements in advertising. In addition, this study reveals the interaction of these elements to create an image of feminine meaning which is defined as feminine, regarding or resembling women. The data are beauty advertisements from Jafra, such as face masks, facial serums, foundations or powders, lipsticks, and perfumes. This study uses Charles Sanders Pierce’s semiotic analysis to translate the meaning of symbols in advertisements for JAFRA women’s beauty products. According to Peirce, a set of semiotics consisting of three main elements is called the triangle theory of meaning (sign, context, and meaning). This study uses a qualitative descriptive objective to provide a systematic, factual, and accurate description of certain facts. The results of this study indicate that in advertisements for JAFRA women’s beauty products, femininity is represented by the visual appearance of the model (person) used, behavior, clothing, poses in the picture, long hair loose, use of image background, colors, displayed, the typeface used in the advertisement image, graceful, spoiled, sexy, flirty and sensitive side of women's femininity, self-expression such as applying makeup, taking care of the face, and body in the picture ads displayed.